2011
DOI: 10.1158/0008-5472.can-10-1303
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Sialyltransferase Inhibitor Suppresses FAK/Paxillin Signaling and Cancer Angiogenesis and Metastasis Pathways

Abstract: Increased sialyltransferase (ST) activity promotes cancer cell metastasis, and overexpression of cell surface sialic acid correlates with poor prognosis in cancer patients. To seek therapies targeting metastasis for cancer treatment, we developed a novel ST inhibitor, Lith-O-Asp, and investigated its antimetastatic and antiangiogenic effects and mechanisms. We found that cells treated with Lith-O-Asp showed a reduction of activity on various ST enzymes by in vitro and cell-based activity analyses. Lith-O-Asp i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
79
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 40 publications
6
79
0
1
Order By: Relevance
“…The increased ␣2,6-linked sialylation on ␤1-integrins also has been reported in several transformed cell types and is postulated to alter integrin function by enhancing its activation state and binding to collagen (17)(18)(19). In these studies, increases in ␣2,6-linked sialylation levels have been correlated with enhanced cell motility and invasiveness in vitro.…”
mentioning
confidence: 73%
“…The increased ␣2,6-linked sialylation on ␤1-integrins also has been reported in several transformed cell types and is postulated to alter integrin function by enhancing its activation state and binding to collagen (17)(18)(19). In these studies, increases in ␣2,6-linked sialylation levels have been correlated with enhanced cell motility and invasiveness in vitro.…”
mentioning
confidence: 73%
“…For example, inhibition of paxillin phosphorylation by the sialytransferase inhibitor Lith-O-Asp or other small molecules suppress lung tumor progression and metastasis (Chen et al, 2011;Huang et al, 2012), as well as breast cancer progression (Golubovskaya et al, 2008), in vivo. Interestingly, these molecules affect phosphorylation activity in the N-terminal region of paxillin, and we have shown here and in a previous study that the expression of the N-terminal alone substantially increases migration when transfected into paxillin knockdown cells, where N-terminus and C-terminus of paxillin have been shown to have complementary but opposite effects on cell migration and invasion (Sero et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Paxillin and FAK are two key signaling molecules in integrin-mediated signaling pathways and are closely associated with cell adhesion, tumor cell migration, cell proliferation and cell survival (8)(9)(10)(11). Some studies have shown that FAK plays a significant role in the integrin signaling pathway (12).…”
Section: Discussionmentioning
confidence: 99%